'God is in the details': visual culture of closeness in the circle of Cardinal Reginald Pole. Issue 5 (14th July 2015) - de la Verpillière, Lorraine
Abstract: As one of the most important political and religious figures of the mid sixteenth century, Cardinal Reginald Pole (1500–58) has been the subject of valuable historical studies. Although the English prelate was also a humanist, part of a vast intellectual and artistic network he established during his travels to Italy, Flanders, Spain and England, Pole has yet to receive the attention he deserves in History of Art. This article aims at re‐appreciating the artistic patronage of the cardinal, in spite of the difficulties raised by the lack of surviving artworks he commissioned and his apparent insensitivity to visual arts. It will be shown that Pole and his religious circle, the spirituali, tried to develop a visual culture of their own, influenced by their religious beliefs and meditational practices. Building on Michelangelo's famous presentation drawings to Vittoria Colonna – the Pietà and the Crucifixion – as well as on painted and drawn works deriving from them by the hand of other artists, this paper examines Pole and his friends' preference for sober, small‐sized and confidential artworks, suggesting the genre of the miniature as a promising avenue of research as regards to Pole's patronage.